Dampak Peraturan Tentang Akses Informasi Keuangan Untuk Kepentingan Perpajakan Terhadap Prinsip Rahasia Bank - Arfianna Novera (Universitas Sriwijaya, 2018)
Government Regulation in Lieu of Law (PERPPU) Number 1 Year 2017 regulates the Authority of the Director General of Tax the Ministry of Finance has access to financial information for tax purposes. This information can be obtained from financial service institutions carrying out activities in the banking sector, capital market, insurance, other financial service institutions and/or other entities categorized as financial institutions. Through this Government Regulation, the government also eliminates the confidentiality rules of financial service institutions related to opening financial access of customers or taxpayers as contained in Article 2 Paragraph stating in terms of financial service institutions, other financial service institutions, and/or other entities as referred to Paragraph 1 are bound by the obligation to keep confidential based on the provisions of the laws and regulations, the confidentiality obligation does not apply in implementing the Government Regulation. The state of urgency also means that in the General Provisions and Taxation Procedure law regulates data access through requests (by request) and only covers the purpose of inspection, investigation and collection of taxes, precisely here the problem lies in the absence of accurate initial data tax audits are not effective and prone to cause disputes that are endless winding. The government guarantees the confidentiality of public data submitted by financial institutions to the DGT, tax officials who divulge confidential taxpayers and use the information for purposes other than fulfilling tax obligations, will be subject to sanctions according to general provisions and taxation procedures.